Handover patterns: an observational study of critical care physicians - Ilan Roy; LeBaron Curtis D; Christianson Marlys K; Heyland Daren K; Day Andrew; Cohen Michael D (BMC, 2012)
Abstract Background Handover (or 'handoff') is the exchange of information between health professionals that accompanies the transfer of patient care. This process can result in adverse events. Handover 'best practices', with emphasis on standardization, have been widely promoted. However, these recommendations are based mostly on expert opinion and research on medical trainees. By examining handover communication of experienced physicians, we aim to inform future research, education and quality improvement. Thus, our objective is to describe handover communication patterns used by attending critical care physicians in an academic centre and to compare them with currently popular, standardized schemes for handover communication. Methods Prospective, observational study using video recording in an academic intensive care unit in Ontario, Canada. Forty individual patient handovers were randomly selected out of 10 end-of-week handover sessions of attending physicians. Two coders independently reviewed handover transcripts documenting elements of three communication schemes: SBAR (Situation, Background, Assessment, Recommendations); SOAP (Subjective, Objective, Assessment, Plan); and a standard medical admission note. Frequency and extent of questions asked by incoming physicians were measured as well. Analysis consisted of descriptive statistics. Results Mean (± standard deviation) duration of patient-specific handovers was 2 min 58 sec (± 57 sec). The majority of handovers' content consisted of recent and current patient status. The remainder included physicians' interpretations and advice. Questions posed by the incoming physicians accounted for 5.8% (± 3.9%) of the handovers' content. Elements of all three standardized communication schemes appeared repeatedly throughout the handover dialogs with no consistent pattern. For example, blocks of SOAP's Assessment appeared 5.2 (± 3.0) times in patient handovers; they followed Objective blocks in only 45.9% of the opportunities and preceded Plan in just 21.8%. Certain communication elements were occasionally absent. For example, SBAR's Recommendation and admission note information about the patient's Past Medical History were absent from 22 (55.0%) and 20 (50.0%), respectively, of patient handovers. Conclusions Clinical handover practice of faculty-level critical care physicians did not conform to any of the three predefined structuring schemes. Further research is needed to examine whether alternative approaches to handover communication can be identified and to identify features of high-quality handover communication.